Urban Forests in Florida: Do They Reduce Air Pollution? - Francisco Escobedo (EDIS)
FOR-128, a 3-page fact sheet by Francisco Escobedo, presents the factors behind pollution removal by trees, estimates the amount of air pollution removal for three Florida cities, and presents strategies for managing urban trees for air quality improvement. Published by the UF School of Forest Resources and Conservation, October 2007.